Health and Awareness among College Students - Naveen Kumar Bhardwaj, (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2013)
The health awareness includes different protective measures to maintain and improve health. Extreme objective of the informative wellbeing administrations program is the fulfillment of physical, mental and profound strength of each and every understudy to the ideal level, which empowers them to get helpful wellbeing propensities. The quality and the amount of strength of an individual relies on the states of human body, on the off chance that it isn't in good shape, ideal result can't be anticipated. To guarantee typical and sound state of being of the understudies, the guardians, instructors and society need to assume the key part.